Historyk jako tłumacz - Sánchez-Marcos, Fernando (Er(r)go. Teoria - Literatura - Kultura, 2001)
Fernando S6nches-Marcos The Historian as Translator This essay focuses on the possibilities faced by the historian as well as the limitations and requirements that he must face in his capacity as a translator of one culture into another. Fernando SanchesMarcos's project takes its inspiration from dialogical hermeneutics as presented in the works of Hans-Georg Gadamer and Paul Ricoeur. At the same time Fernando Sanches-Marcos incorporates into his discussion our contemporary experience of technology and economic globalisation. Those aspects of the world in which the historian lives make it necessary for him to sustain and cultivate the dialogue between cultures. Fernando Sanches-Marcos postulates that historians should erect bridges of understanding between various groups of people and various temporal perspectives. Thus historians could help their contemporaries get used to a peaceful coexistence in a multicultural society. In Fernando Sanches-Marcos's view, the historian's responsibility is so much the greater that the future of all humanity, not only the Western civilisation, is at stake here.